3-D human face modeling for dynamic facial expression synthesis - Zhang, Yu. (2008)
This thesis consists of 2 part. -Part B-. This thesis describes a computer system for dynamically synthesizing realistic facial expres-sions using a new 3D human face model constructed from the anatomical perspective. Like real human face, the face model has a hierarchical structure, incorporating a physically-based approximation to facial skin tissue, a set of anatomically-motivated facial muscle actuators and underlying skull structure.